The Effect of Lecturer Professionalism and Quality of Academic-Administrative Services on Student Satisfaction with The Mediation of Student Comfort At STIT Pringsewu - Diena Izzaty Muslih; Zainul Kisman (Global Academy of Business Studies, 2026)
Purpose: This study aimed to examine the effects of lecturer professionalism and academic–administrative service quality on student satisfaction, with student comfort serving as a mediating variable at STIT Pringsewu. Research Methodology: This study used a quantitative approach with a cross-sectional design. Primary data were collected through questionnaires administered to active undergraduate students in Semesters 4 and 6. A purposive sampling technique was used with 347 respondents from a population of 2,619 students. Data analysis was performed using Partial Least Squares structural equation modeling (PLS-SEM). Results: The results showed that lecturer professionalism and academic–administrative service quality significantly affect student satisfaction, both directly and indirectly through student comfort as a mediating variable. The endogenous construct "Student Comfort" has an R-square value of 0.570, and "Student Satisfaction" has an R-square value of 0.781. Conclusions: Lecturer professionalism and academic–administrative service quality are essential in improving student satisfaction, with student comfort acting as an effective mediator. Continuous improvements in service delivery, responsiveness, and empathy in academic–administrative services are recommended to enhance student satisfaction and comfort. Limitations: The study was conducted at STIT Pringsewu, limiting generalizability. The purposive sampling technique may affect sample representativeness. Contribution: This study provides insights into the roles of lecturer professionalism and academic–administrative service quality in shaping student satisfaction and highlights the importance of student comfort as a mediating factor.